Identification problems in personality psychology - Lex Borghans; Bart Golsteyn; James J. Heckman; John Eric Humphries (Institute for the Study of Labor (IZA), 2011)
This paper discusses and illustrates identification problems in personality psychology. The measures used by psychologists to infer traits are based on behaviors, broadly defined. These behaviors are produced from multiple traits interacting with incentives in situations. In general, measures are determined by these multiple traits and do not identify any particular trait unless incentives and other traits are controlled for. Using two data sets, we show, as an example, that substantial portions of the variance in achievement test scores and grades, which are often used as measures of cognition, are explained by personality variables.
urn:nbn:de:101:1-201104134432
Keywords: D01; D03; D89; 330; identification problem; personality; psychology; achievement test; grades; Persönlichkeitspsychologie; Intelligenz; Messung; Theorie